Renata Wasserman and Inter-Americanism - Earl E. Fitz (Ilha do Desterro, 2022)
This essay considers Prof. Wasserman as a practitioner of the field known, variously, as inter-American literary study, hemispheric literature, and the literature of the Americas. It also argues that she is a leader in this field because of her discerning critical observations but also because she proves the singular importance of Brazilian letters in this comparatively American perspective. My study especially celebrates her work on two Brazilian authors: José de Alencar and Mário de Andrade. Wasserman makes clear how these two writers make major contributions to our better understanding of nineteenth and twentieth-century literature in the Americas.